Factors Associated with Occupational Accidents to Nurses in Emergency Room of Anutapura General Hospital Palu City - Salmawati, Lusia; Rasul, Muh.; Napirah, Muhammad Ryman (Preventif: Jurnal Kesehatan Masyarakat, 2019)
The IGD room is a unit that deals directly with the patient for 24 hours a day. Workload and high stress levels in the face of critical conditions require nurses to work quickly and appropriately. Based on data from the preliminary study of the researchers, nurses working in the Emergency Installation Room (IGD) Anutapura Palu General Hospital are 31 nurses, aged between 23-45 years with an average work period of 7 years and the majority male. The data of accidents cases were 81 cases in bracket within 3 months (January-March 2016), and most cases were found in room of IUG Anutapura Palu RSU with 19 cases. The purpose of research to determine the factors associated with the incidence of occupational accidents in nurses in the Emergency Room of Anutapura Palu General Hospital. This research is a kind of quantitative analytic research with Cross Sectional design. Population in this research is all nurses who work in Emergency Room of Anutapura Palu General Hospital that amount 31 people, sampling with technique Total Sampling. The results of the study were age (p = 0,002), sex (p = 0,019), use of APD (p = 0,007), regulation (p = 0,006), training (p = 0,007), supervision (p = 0,006) . However there is no working period relationship (p = 0,083) with Work Accident. It is expected that the management of the hospital to improve the quality of training and supervision and reinforce the rules that have been made by giving heavy sanctions to workers who get violated the rules.